AEG-1 as a Novel Therapeutic Target in Colon Cancer: A Study from Silencing AEG-1 in BALB/c Mice to Large Data Analysis - Sriramulu, Sushmitha; Malayaperumal, Sarubala; Banerjee, Antara; Anbalagan, Muralidharan; Kumar, Makalakshmi M.; Radha, Rajesh K. N.; Liu, Xingyi; Zhang, Hong; Hu, Guang; Sun, Xiao-Feng; Pathak, Surajit (Current Gene Therapy, 2024)
Background: Astrocyte elevated gene-1 (AEG-1) is overexpressed in various malignancies. Exostosin-1 (EXT-1), a tumor suppressor, is an intermediate for malignant tumors. Understanding the mechanism behind the interaction between AEG-1 and EXT-1 may provide insights into colon cancer metastasis. Methods: AOM/DSS was used to induce tumor in BALB/c mice. Using an in vivo-jetPEI transfection reagent, transient transfection of AEG-1 and EXT-1 siRNAs were achieved. Histological scoring, immunohistochemical staining, and gene expression studies were performed from excised tissues. Data from the Cancer Genomic Atlas and GEO databases were obtained to identify the expression status of AEG-1 and itsassociation with the survival. Results: In BALB/c mice, the AOM+DSS treated mice developed necrotic, inflammatory and dysplastic changes in the colon with definite clinical symptoms such as loss of goblet cells, colon shortening, and collagen deposition. Administration of AEG-1 siRNA resulted in a substantial decrease in the disease activity index. Mice treated with EXT-1 siRNA showed diffusely reduced goblet cells. In vivo investigations revealed that PTCH-1 activity was influenced by upstream gene AEG-1, which in turn may affect EXT-1 activity. Data from The Cancer Genomic Atlas and GEO databases confirmed the upregulation of AEG-1 and downregulation of EXT-1 in cancer patients. Conclusions: This study revealed that AEG-1 silencing might alter EXT-1 expression indirectly through PTCH-1, influencing cell-ECM interactions, and decreasing dysplastic changes, proliferation and invasion.
Keywords: EXT-1